Lean production for the small company - Elbert, Mike. (Boca Raton, FL : CRC Press, 2013)
Preface This book is designed to walk companies through the implementation of lean manufacturing within their companies. We start with the fundamentals and build upon them to teach all the tools and processes needed to implement lean manufacturing and the Toyota Production System (TPS). We teach how to determine and calculate the waste in business and manufacturing systems, as well as how to use continuous improvement to implement the changes needed to eliminate wasteful steps and processes. We explain how to remove the variation within business and manufacturing processes to achieve a steady continuous flow of product through a system that more efficiently delivers product on time to customers. Time is spent on how to design factories for lean manufacturing, emphasizing how to use customer order demands to schedule the production floor rather than using estimated production schedules, which can lead to excess inventory and inflexibility in meeting customer demand. New methods and tools are discussed that focus on reducing inventory, improving inventory turns, and improving raw material flow through the factory. Companies are taught how to work and partner with suppliers and customers. One chapter is dedicated to the accounting process and how to improve cash-to- cash cycle time. All the chapters in this book, when implemented, will result in a culture change within your company that will improve business and turn your company into a continuously improving and learning organization that never stops eliminating waste and improving processes. All of this allows companies to grow, without adding the cost of additional space or hiring more people, to become more competitive in the markets they serve.
Includes bibliographical references and index.
Keywords: Lean manufacturing